2012
DOI: 10.3109/08982104.2012.700460
|View full text |Cite
|
Sign up to set email alerts
|

Brain delivery of olanzapine by intranasal administration of transfersomal vesicles

Abstract: The aim of this study was to investigate the presence of a possible direct correlation between vesicle elasticity and the amount of drug reaching the brain intranasally. Therefore, transfersomes were developed using phosphatidylcholine (PC) as the lipid matrix and sodium deoxycholate (SDC), Span® 60, Cremophor® EL, Brij® 58, and Brij® 72 as surfactants. The influence of the type of surfactant and PC-to-surfactant ratio on vesicle morphology, size, membrane elasticity, drug entrapment, and in vitro drug release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
72
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(78 citation statements)
references
References 40 publications
6
72
0
Order By: Relevance
“…For drug loaded bilosomes, the characteristic peak of TX completely disappeared which probably signify that TX was either entrapped inside the bilosomes (Salama et al, 2012;Manne et al, 2014) or completely transformed from crystalline form to molecular state in surfactant mixture. Nasr et al (2008) reported that the absence of drug's crystalline melting peak after encapsulation might also indicate the presence of strong interaction between the surfactant bilayers of the vesicles and the entrapped drug.…”
Section: Transmission Electron Microscopy (Tem)mentioning
confidence: 92%
“…For drug loaded bilosomes, the characteristic peak of TX completely disappeared which probably signify that TX was either entrapped inside the bilosomes (Salama et al, 2012;Manne et al, 2014) or completely transformed from crystalline form to molecular state in surfactant mixture. Nasr et al (2008) reported that the absence of drug's crystalline melting peak after encapsulation might also indicate the presence of strong interaction between the surfactant bilayers of the vesicles and the entrapped drug.…”
Section: Transmission Electron Microscopy (Tem)mentioning
confidence: 92%
“…Moreover, the AUC (0-1) and MRT (0)(1) in the brain after I.N administration of 99m Tc-R7 were significantly higher value compared to I.V administration of 99m Tc-ZT solution (23.28 and 0.89 h%/g) and (36.38 and 9.35 h), respectively (p50.05). This could be explained by the high capability of the lipid nanovesicles to permeate the nasal membrane (Salama et al, 2012;Abdelrahman et al, 2015). This suggests that the nasal route is considered as preferential route for brain targeting than I.V.…”
Section: Animal Studymentioning
confidence: 99%
“…The higher MRT value of 99m Tc-R7 after I.N administration confirms the ability of the novasomes formulation to prolong and control the rate of ZT release over an extended period of time. Lipid nanovesicles have been demonstrated to have good permeability characteristics that enhance nasal penetration of many drugs through disrupting the mucosal membrane, hence increase absorption of drugs (Salama et al, 2012). Intranasal novasomes delivery enhanced ZT delivery to the brain through the olfactory pathway in which it travels from the nasal cavity to brain tissue (Illum, 2000).…”
Section: Animal Studymentioning
confidence: 99%
“…The preparations were administered at the openings of the nostrils (Abd-Elal et al, 2016) using micropipette (200 ml) fixed with low density polyethylene tube having 0.1 mm internal diameter at the delivery site. The procedure was performed gently, allowing the animals to inhale all the preparation (Salama et al, 2012). For I.V administration, 99m Tc-PM7 was injected through the tail vein of Group C mice.…”
Section: Animal Studymentioning
confidence: 99%
“…Samples of pure drug, components (Pluronic Õ P123 and Pluronic Õ L121) and drug-loaded PM (PM7) were heated in an aluminum pan at a rate of 5 C/min in an atmosphere of nitrogen to 400 C and the thermograms were recorded (Salama et al, 2012).…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%